Regulator of telomere length 1 (RTEL1) mutations are associated with heterogeneous pulmonary and extra-pulmonary phenotypes. Issue 2 (7th February 2019) - Borie, Raphael; Bouvry, Diane; Cottin, Vincent; Gauvain, Clement; Cazes, Aurélie; Debray, Marie-Pierre; Cadranel, Jacques; Dieude, Philippe; Degot, Tristan; Dominique, Stephane; Gamez, Anne Sophie; Jaillet, Madeleine; et al.
Regulator of telomere length 1 ( RTEL1 ) mutations have been evidenced in 5–9% of familial pulmonary fibrosis; however, the phenotype of patients with interstitial lung disease (ILD) and RTEL1 mutations is poorly understood. Whole exome sequencing was performed in 252 probands with ILD and we included all patients with ILD and RTEL1 mutation. RTEL1 expression was evaluated by immunochemistry in the lungs of controls, as well as in RTEL1 and telomerase reverse transcriptase ( TERT ) mutation carriers. We identified 35 subjects from 17 families. Median age at diagnosis of ILD was 53.1 years (range 28.0–80.6). The most frequent pulmonary diagnoses were idiopathic pulmonary fibrosis (n=20, 57%), secondary ILD (n=7, 20%) and unclassifiable fibrosis or interstitial pneumonia with autoimmune features (n=7, 20%). The median transplant-free and overall survival periods were 39.2 months and 45.3 months, respectively. Forced vital capacity at diagnosis was the only factor associated with decreased transplant-free survival. Extra-pulmonary manifestations were less frequent as compared to other telomere-related gene mutation carriers. A systematic analysis of the literature identified 110 patients with ILD and RTEL1 mutations (including this series) and confirmed the heterogeneity of the pulmonary phenotype, the prevalence of non-idiopathic diseases and the low prevalence of extra-pulmonary manifestations. Immunohistochemistry showed that RTEL1 was expressed by bronchial and alveolar epithelial cells, as well as by alveolar macrophages and lymphocytes, but not by fibroblasts. RTEL1 mutations are associated with heterogeneous lung phenotypes with limited and heterogeneous extra-respiratory manifestations http://ow.ly/1Ssr30mCZjx